(untitled) (Eurasian Scientific Herald, 2024)
A healthy lifestyle ensures human development and health. It has a beneficial effect on the physiological and mental states of students. Our research was aimed at certain influencing factors, students’ performance and noncompliance with a healthy lifestyle.